2011
DOI: 10.1007/s00262-011-1172-6
|View full text |Cite
|
Sign up to set email alerts
|

An immune-active tumor microenvironment favors clinical response to ipilimumab

Abstract: These results support the proposed mechanism of action of ipilimumab, suggesting that cell-mediated immune responses play an important role in the antitumor activity of ipilimumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
492
4
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 686 publications
(547 citation statements)
references
References 45 publications
29
492
4
8
Order By: Relevance
“…However, when these responses are assessed in the context of the distinct tumor microenvironments observed across the preclinical models, our results are broadly in agreement with clinical findings, which demonstrate an association between CD8 + T-cell infiltration into the tumor and outcome following immune-checkpoint blockade (9,48,49). Indeed, our work also revealed that tumors such as CT26, in which the immune infiltrate contains greater numbers of cytotoxic immune cells such as CD8 + T cells and NK cells, were more responsive to immunecheckpoint blockade than those with comparatively little immune or predominantly immunosuppressive infiltrate.…”
Section: Discussionsupporting
confidence: 80%
“…However, when these responses are assessed in the context of the distinct tumor microenvironments observed across the preclinical models, our results are broadly in agreement with clinical findings, which demonstrate an association between CD8 + T-cell infiltration into the tumor and outcome following immune-checkpoint blockade (9,48,49). Indeed, our work also revealed that tumors such as CT26, in which the immune infiltrate contains greater numbers of cytotoxic immune cells such as CD8 + T cells and NK cells, were more responsive to immunecheckpoint blockade than those with comparatively little immune or predominantly immunosuppressive infiltrate.…”
Section: Discussionsupporting
confidence: 80%
“…A limiting factor in immune therapy is the insufficient homing of T cells to the tumor site. Many of the new immune therapies either require the presence of pre-existing T cells in the tumor, 12 , 26 , 27 or rely on sufficient tumor homing of tumor specific T cells after peripheral or in vitro activation. 14 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the observation that intratumoural antitumour inflammation is triggered after secretion of IFNγ by infiltrating CD8 + T cells 99 , a profile referred to as the 'T-cell-inflamed tumour microenvironment' has been associated with response to diverse immunotherapies, including vaccines, IL-2, as well as anti-CTLA-4 and anti-PD-1 antibodies [138][139][140][141] . This concept has been applied broadly in melanoma and beyond (in gastric, head and neck, and urothelial cancers), with multiple reports from the 2015 ASCO meeting indicating not only that increasing IFNγ-associated gene-expression scores are predictive of a response to pembrolizumab, but also, perhaps more importantly, that the lack of IFNγ-associated gene expression is very highly correlated with lack of clinical benefit 100,[142][143][144] .…”
Section: Braf-mek-inhibitor Resistance and Biomarkersmentioning
confidence: 99%